Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jpcc.6b05856
|View full text |Cite
|
Sign up to set email alerts
|

Structure Prediction of Self-Assembled Dye Aggregates from Cryogenic Transmission Electron Microscopy, Molecular Mechanics, and Theory of Optical Spectra

Abstract: Cryogenic transmission electron microscopy (cryo-TEM) studies suggest that TTBC molecules self-assemble in aqueous solution to form single-walled tubes with a diameter of about 35 Å. In order to reveal the arrangement and mutual orientations of the individual molecules in the tube, we combine information from crystal structure data of this dye with a calculation of linear absorbance and linear dichroism spectra and molecular dynamics simulations. We start with wrapping crystal planes in different directions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 53 publications
1
60
1
Order By: Relevance
“…In many cases, the simulated optical spectra present good agreement with the experimental measurements when disorder is taken into account. 43 , 207 Also note that the CD signal calculated by exciton methods typically covers only the supramolecular component of the signal and molecular chirality should be subtracted. However, many studies have demonstrated that the induced CD signal by assembly is generally significantly different or larger than the molecular component, such as for protein secondary structure determination 208 and achiral molecules forming helical assemblies.…”
Section: Comparison Of Simulation and Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, the simulated optical spectra present good agreement with the experimental measurements when disorder is taken into account. 43 , 207 Also note that the CD signal calculated by exciton methods typically covers only the supramolecular component of the signal and molecular chirality should be subtracted. However, many studies have demonstrated that the induced CD signal by assembly is generally significantly different or larger than the molecular component, such as for protein secondary structure determination 208 and achiral molecules forming helical assemblies.…”
Section: Comparison Of Simulation and Experimental Resultsmentioning
confidence: 99%
“…In practice, this means that the initial configurations are under a lot of stress, leading either to numerical instabilities or causing distortion or even disintegration of the aggregate. Careful minimization and equilibration runs are therefore usually required, The work of Megow et al 43 on J-aggregates provides a nice example of this procedure. They use different wrapping and packing motifs to create aggregates of tetrachloro-tetraethyl-benzimidacarbocyanine (TTBC) dyes.…”
Section: Molecular Simulation Techniquesmentioning
confidence: 99%
“…The Stokes shift is also reasonably large compared to the width of the J‐band. Another promising aggregate is the cyanine derivative 5,5′,6,6′‐ tetrachloro‐1,1′,3,3′‐tetraethyl‐benzimidacarbocyanine (TTBC) …”
Section: Discussionmentioning
confidence: 99%
“…Another promising aggregate is the cyanine derivative 5,5 0 ,6,6 0 -tetrachloro-1,1 0 ,3,3 0 -tetraethyl-benzimidacarbocyanine (TTBC). [28] As mentioned above, in principle one has a large tunability of the properties of the JH-aggregate by choosing appropriate molecules and designing specific arrangements. In this way, nowadays one has the possibility to tailor the spectral properties in order to produce the JH-aggregates most suited for use in LSCs.…”
Section: Discussionmentioning
confidence: 99%
“…According to cryo-transmission electron microscopy, TTBC-Cl forms single-walled tubes with a diameter of only 35 Å and lengths in the µm range [3]. Recently, a molecular structure was suggested, consistent with these dimensions and the absorption and LD spectra [5]. The structure is helical, formed by rings of six monomeric units with transition dipoles aligned 74° to the longitudinal aggregate axis, and an interring slip of 30°.…”
mentioning
confidence: 94%